Overexpression of the activated form of the AtAREB1 gene (AtAREB1 Delta QT) improves soybean responses to water deficit - Leite, J. P. [UNESP]; Barbosa, E. G. G.; Marin, S. R. R.; Marinho, J. P.; Carvalho, J. F. C.; Pagliarini, R. F.; Cruz, A. S.; Oliveira, M. C. N.; Farias, J. R. B.; Neumaier, N.; Guimaraes, F. C. M.; Yoshida, T.; et al. (Funpec-editora, 2014)
Abscisic acid-responsive element binding protein (AREB1) is a basic domain/leucine zipper transcription factor that binds to the abscisic acid (ABA)-responsive element motif in the promoter region of ABA-inducible genes. Because AREB1 is not sufficient to direct the expression of downstream genes under non-stress conditions, an activated form of AREB1 (AREB1 Delta QT) was created. Several reports claim that plants overexpressing AREB1 or AREB1 Delta QT show improved drought tolerance. In our studies, soybean plants overexpressing AREB1 Delta QT were characterized molecularly, and the phenotype and drought response of three lines were accessed under greenhouse conditions. Under conditions of water deficit, the transformed plants presented a higher survival rate (100%) than those of their isoline, cultivar BR 16 (40%). Moreover, the transformed plants displayed better water use efficiency and had a higher number of leaves than their isoline. Because the transgenic plants had higher stomatal conductance than its isoline under well-watered conditions, it was suggested that the enhanced drought response of AREB1 Delta QT soybean plants might not be associated with altered transpiration rates mediated by ABA-dependent stomatal closure. However, it is possible that the smaller leaf area of the transgenic plants reduced their transpiration and water use, causing delayed stress onset. The difference in the degree of wilting and percentage of survival between the 35S-AREB1 Delta QT and wildtype plants may also be related to the regulation of genes that protect against dehydration because metabolic impairment of photosynthesis, deduced by an increasing internal CO2 concentration, was not observed in the transgenic plants.
Keywords: AtAREB1 Delta QT; Biolistics; Drought tolerance; Soybean; Transcription factor; Water use efficiency